HALLAZGO EN CHILE DE STUARDOSATYRUS WILUAMSIANUS (BUTLER), 1868, Y CONSIDERACIONES SOBRE EL GENERO (LEPIDOPTERA: SATYRIDAE) - Herrera G., José; Pérez D’A., Vicente (Acta Entomológica Chilena, 2022)
A.C. Buller (1868) described Argyrophorus williamsianus nov., on one specimen collecled by Charles Darwin at “Port Famine", Strail of Magellan. Most Chilean and European Lepidopterologisls for ihe past 100 years have noi properlv recognized this species, although E. Creta in this Catalogue (1965) memions it as present from “Nuble (Termas de Chillán) down lo Pon Famine (Strait of Magellan)''. J. Herrera (1962) during his visit to the British Museum (Natural History) had the privilege to examine all the material of this species kept there, and except for the Darwin's examplc coming from Pon Famine, all the resl were collected from cióse argentinian localities. In his paper J. Herrera described a new genus, Stuardosatyrus, to hold Butler's species, under which new combination it is now referred to. Professor Vicente Pérez D'A, from 1981 on, has collected abnut 30 specimens of both sexes all coming from “Planicies Orientales" with coid climate steppe (BSk’). in actual Chilean lerritorv. The female genitalia of S. williamsianus (Butler) is herein described and illuslrated for the First time, as wcll as the wing venalion and genitalia of cióse allied genera lo which williamsianus has often be assigned to. Photographs of S. williamsianus and of the types ol Etchevemus chiliensis magallamrus Herrera, are also included.